PENENTUAN POTENSI BAHAYA DAN TITIK KENDALI KRITIS (CRITICAL CONTROL POINT) PADA PROSES PRODUKSI AYAM GORENG SUHARTI - , DWI NOFIA RAHMAWATI, Dr.Ir.Wahyu Supartono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of restaurant based fried chicken, recently, is booming. There are various flavors and serving method given by business player to attract consumerâs intention. Aside of having higher nutrition, fried chicken is a wellâliked product by the ranging of age of consumer started from children to adult. The usage of local chicken considers precisely since it has lower fat and the meat is more rubbery than broiler. Therefore, the analysis is necessarily conducted to decide the risk potency often met in the production process that can potentially increase the risk of product safety. Ayam Goreng Suharti Restaurant is one of legendary restaurants in culinary, mainly in Yogyakarta. As one of culinary businesses, Ayam Goreng Suharti Restaurant can implement a safety food management, HACCP(Hazard Analysis Critical Control Point) principle. One of HACCP principles is to decide critical control point or CCP. The decision of CCP is performed by using HACCP Analysis Check Sheet and Decision Tree. CCP is stated in every process starting from the beginning to final of production process, and select the limit of critical control point in any stage that can potentially result any hazard. CCP in the final production process of fried chicken is at frying and leaking stage. The available hazard potency may result health disturbance for consumer. The critical limit stated is the using of edible oil that is not more than twice, and the leaking is done until the last oil left in the product.